Proposals for Annual Plan 1972-73 Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1972)
The Fourth Five year Plan for the Union Territory of Andaman and Nicobar islands was formulated, taking into account the relative backwardness of the area and its isolation from the. Mainland. This territory was beset with problems like shortage of drinking water, inadequate communication facilities, insufficient milk supply, lack of jetties and harbour facilities; in interisland vessels. There was also the need for increasing the food production and improving medical and educational facilities.
Planning Commission
Andaman and Nicobar Administration